Analisis Hukum Mengenai Turunnya Balik Nama Sertifikat Hak Milik Menjadi Hak Guna Bangunan pada Badan Usaha Atau Perseroan Terbatas (PT) - Anjelina Sitinjak; Novri Yanti Elisabeth Sirait; Muhammad Fajar Hidayat (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Land is something that is very meaningful for the lives of living creatures, especially humans, from the past until the future. Therefore, it is important to have clear legal rules to regulate it. In Article 16 paragraph (1) of the UUPA, there are several types of land rights, namely: Ownership Rights, Cultivation Rights, Building Use Rights, and Use Rights, Rental Rights, Land Clearance Rights, and Forest Product Harvesting Rights. Land rights are rights owned by every land owner provided they have a certificate as strong evidence. Property rights are the strongest and most fulfilled rights. Business entities in the form of limited liability companies are currently in great demand, but problems often occur regarding land use due to the reduction in the status of Land Ownership Rights to Building Use Rights experienced by limited liability companies. The transition process also often experiences obstacles. For this reason, this research uses normative juridical research methods which focus on studying the application of rules or norms in positive law with a statutory approach and legal norms relating to land rights by Limited Liability Companies.